Risco de financeirização das rendas petrolíferas: a renegociação da dívida do Estado do Rio de Janeiro junto à União - Lira, Gustavo Carvalho Tapia (2011)
This study consists in analysis of the application of oil revenues in Brazil. Depart from the hypothesis that this application should be attentive to the intergenerational justice, as it is a non-renewable mineral resource and much of its use should be invested in public policy on future generations. Our analysis will focus on the capture of these rents by the State of Rio de Janeiro, in the form of royalties and special taxes which were used to pay the public debt with the Federal Government as part of the fiscal adjustment program. In our investigation, the application of these rents, justified in the interests of macroeconomic equilibrium, it can be explain by the fundamentals elements of contemporary capitalism, the financialization"